Effect of Urethral Dilation in Women with Lower Urinary Tract Symptoms - Phimphilai, Prempong; Ramart, Patkawat; Soontrapa, Suchai; Nualyong, Chaiyong; Leewansangtong, Sunai; Srinualnad, Sittiporn; Taweemonkongsap, Tawatchai; Chaiyaprasithi, Banasithi; Amornvesukit, Teerapon; Jitpraphai, Siros; Phinthusophon, Kittipong; Sujijantararat, Phichaya; et al. (Insight Urology, 2016)
Objective: To evaluate the effect of urethral dilation on lower urinary tract symptoms in women. Material and Methods: Forty-five women with non-neurogenic lower urinary tract symptoms (LUTS) without genital prolapsed underwent urethral dilation. Clinical and uroflowmetry were followed up and recorded at 1 and 3 months. Any significant change in clinical and uroflowmetry were evaluated. Results: Within 1 month of dilation, 88% (40/45) of the women reported a clinical improvement. Clinical improvement in LUTS was associated with a lower IPSS score (p<0.05). At 3 months, 80% (36/45) of the women also reported a clinical improvement. No significant change in uroflowmetry before and after dilation was reported. Conclusion: The study demonstrated that urethral dilation was effective in aged women with LUTS in the short term (1 and 3 months) However, other studies are reguired in order to determine the long-term effects. ผลของการขยายท่อปัสสาวะในผู้หญิงวัยกลางคน ที่มีกลุ่มอาการทางเดินปัสสาวะส่วนล่าง เปรมพงษ์ พิมพ์พิไล, ภควัฒน์ ระมาตร์, สุชาย สุนทราภา, ไชยยงค์ นวลยง, สุนัย ลีวันแสงทอง, สิทธิพร ศรีนวลนัด, ธวัชชัย ทวีมั่นคงทรัพย์, บรรณสิทธิ์ ไชยประสิทธิ์, ธีระพล อมรเวชสุกิจ, ศิรส จิตประไพ, กิตติพงษ์ พินธุโสภณ, พิชัย ศุจิจันทรัตน์, เอกรินทร์ โชติกวาณิชย์, นพเก้า ชนะภัย สาขาวิชาศัลยศาสตร์ยูโรวิทยา ภาควิชาศัลยศาสตร์ คณะแพทยศาสตร์ศิริราชพยาบาล มหาวิทยาลัยมหิดล กรุงเทพฯ บทคัดย่อ วัตถุประสงค์: เพื่อประเมินผลของการขยายท่อปัสสาวะในผู้หญิงอายุมากกว่า 40 ปีและอาการทางเดินปัสสาวะส่วนล่าง ผู้ป่วยและวิธีการศึกษา: ผู้หญิง 45 คน ที่มีอาการทางเดินปัสสาวะส่วนล่างได้มารับการรักษาด้วยวิธีขยายท่อปัสสาวะ โดยทุกราย ได้รับการประเมินอาการและความแรงของการปัสสาวะ (uroflowmetry) ก่อนและหลังขยายท่อปัสสาวะที่ 1 และ 3 เดือน ผลการศึกษา: ร้อยละ 88 มีอาการทางเดินปัสสาวะส่วนล่างดีขึ้นที่ 1 เดือนหลังขยายท่อปัสสาวะ โดยร้อยละ 80 ยังคงมีอาการ ทางเดินปัสสาวะส่วนล่างดีที่ 3 เดือนหลังขยายท่อปัสสาวะ แต่ไม่พบการเปลี่ยนแปลงความแรงของการปัสสาวะ (uroflowmetry) สรุป: การขยายท่อปัสสาวะสามารถช่วยให้อาการทางเดินปัสสาวะส่วนล่างในผู้หญิงดีขึ้นได้ในระยะสั้น (ที่ 1 และ 3 เดือน) ส่วน ผลในระยะยาวยังต้องศึกษาเพิ่มเติมต่อไป